2007
DOI: 10.1002/jso.20734
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of perinodal extension in gastric cancer

Abstract: The perinodal extension was the most important independent prognostic factor in gastric cancer, and should be included in the TNM gastric cancer staging system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
7
1
Order By: Relevance
“…This study shows that ENE is associated with advanced T and N category, larger tumour size and lymphovascular/perineural invasion. This is in agreement with other studies showing that ENE is related closely to tumour aggressiveness. The association with male sex may be due to the fact that more men had tumours of advanced stage.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study shows that ENE is associated with advanced T and N category, larger tumour size and lymphovascular/perineural invasion. This is in agreement with other studies showing that ENE is related closely to tumour aggressiveness. The association with male sex may be due to the fact that more men had tumours of advanced stage.…”
Section: Discussionsupporting
confidence: 94%
“…Only lymph node‐positive gastric cancers were included in the present study to clarify the prognostic significance of ENE. All previous studies on ENE in gastric carcinoma included node‐negative patients, and the actual numbers of node‐positive cases with ENE were much lower than in the present study.…”
Section: Discussioncontrasting
confidence: 77%
“…Extranodal spread in metastatic lymph nodes has been observed in cancers of such organs as the pharynx, larynx, stomach, and rectum, and has been drawing attention as a negative prognostic factor [2][3][4][5]7]. The definition of extranodal spread, however, varies with the investigator and has not been standardized yet.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that extranodal spread is a prognostic factor in patients with several solid cancers [2][3][4], and such reports on gastric cancer have also been increasing in recent years [5][6][7]. However, the definition of extranodal spread varies with the reporting investigator and has not been standardized yet.…”
Section: Introductionmentioning
confidence: 93%
“…ENTE in metastatic lymph nodes is widely regarded as a poor prognostic factor in many malignancies including gastric cancer [ 4 , 12 ], bladder cancer [ 13 , 14 ], papillary thyroid carcinoma [ 15 ], penile carcinoma [ 8 ], breast cancer [ 16 ], non-small cell lung cancer [ 17 ], and prostate cancer [ 18 ]. Lee et al and Choi et al reported that ENTE is associated with advanced T and N stages and is an independent factor for poor prognosis in gastric cancer [ 4 , 12 ]. Fleischmann et al and Fajkovic et al reported that ENTE is an independent prognostic factor for bladder cancer patients with lymph node metastasis, especially with disease recurrence [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%